GLOBALIZATION CHALENGGE AND STRATEGY OF INCREASING TAX TO FACE ASEAN ECONOMIC COMMUNITY - Hardianto, Ade Manggala (Prosiding Seminar Nasional INDOCOMPAC)
ASEAN as region organization considers the important of regional integration. In accordance with this, ASEAN representatives have create the ASEAN VISION 2020, which is based on three principles, political, economic and social culture. Globalization is the biggest challenge for every nation that needs to be anticipated, there are 10 (ten) challenge that Indonesia  has to face, such as economis globalization, unemployment, social responsibility, environment preservation, living standar improvement, etcnic and moral norms implementations, labour diversity, demography configuration, scinence and technologi and political challenge. Therefore, the strategy to improve the is by expanding the receipt base, strengthing the collection process,  improving  the capacity of local income, improving of supervising process, improving the receipt capacity through  better planning, improving the countinousness of tax or retribution payer and mapping the receipt potention. Keywords : challenge, globalization and strategy ASEAN sebagai sebuah organisasi regional menyadari pentingnya suatu integrasi kawasan. Sejalan dengan hal tersebut, para wakil ASEAN membuat ASEAN Visions 2020 yang berdasar pada tiga pilar yaitu keamanan politik, ekonomi, dan sosial-budaya. Terdapat tiga komunitas dalam ASEAN Community yang sesuai dengan tiga pilar dari ASEAN Vision 2020, yaitu pada bidang keamanan politik (ASEAN Political-Security Community), ekonomi (ASEAN Economic Community), dan sosial budaya (ASEAN Socio-Culture Community) Globalisasi merupakan tantangan terbesar bagi semua Negara, dan diperlukan  memperhitungkan tantangan tersebut. Ada 10 tantangan yang harus dihadapi oleh Indonesia Tantangan globalisasi ekonomi, Pengangguran Tanggungjawab social, Pelestarian lingkungan hidup, Peningkatan mutu hidup,Penerapan norma-norma moral dan etika Keanekaragaman tenaga kerja Konfigurasi demografi, Penguasaan dan pemanfaaatan iptek dan tantangan bidang politik Adapun strategi peningkatan pajak daerah dengan cara memperluas basis penerimaan, memperkuat proses pemungutan, peningkatan kapasitas pengelola penerimaan daerah, meningkatkan pengawasan, meningkatkan kapasitas penerimaan melalui perencanaan yang lebih baik,  meningkatkan kesadaran wajib pajak/retribusi,  dan memetakan potensi penerimaan. Keyword : Tantangan, Globalisasi, Strategi Pendapatan Daerah